The transformational leadership style towards employees’ performance at Majlis Bandaraya Melaka Bersejarah (MBMB) - Naziron, Nur Hidayati; Abdul Rahman, Nurfarah Izzati (2012)
In this 21st century, there is no doubt that leadership is essential to ensure the high performance of employees. Employees are a human being that needs motivation, encouragement and support to boost up their effort into the organizational achievement. Since there are several reformation programs implemented by the government into the public sector, leadership become more important as the leader will become the catalyst to change employees’ ways of working as well as the organizational culture. Therefore, this research is conducted to study the contribution of transformational leadership into the employees’ performance.